Recent Analyses of Annual Wage Guarantees - Campbell, Rita Ricardo (Quarterly Journal of Economics, 1948)
Journal Article Recent Analyses of Annual Wage Guarantees Get access Rita Ricardo Campbell Rita Ricardo Campbell Tufts College Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 62, Issue 4, August 1948, Pages 542–561, https://doi.org/10.2307/1881764 Published: 01 August 1948